2011
DOI: 10.1245/s10434-011-1850-9
|View full text |Cite
|
Sign up to set email alerts
|

Is Port Site Resection Necessary in the Surgical Management of Gallbladder Cancer?

Abstract: In patients with incidental GBCA, port site metastases were associated with peritoneal disease and decreased survival. Port site resection was not associated with improved survival or disease recurrence and should not be considered mandatory during definitive surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(77 citation statements)
references
References 20 publications
1
74
1
1
Order By: Relevance
“…Paolucci et al reported an incidence of 17.1 % port site recurrence over a median period of 6 months after LC [14]. In a recent retrospective study from Memorial Sloan Kettering Cancer Centre, 69 patients after LC underwent definitive surgery with port site resection [18]. Port site recurrence was found in 13 patients (19 %) with T2 and T3 tumours.…”
Section: Laparoscopic Cholecystectomy and Port Site Recurrencementioning
confidence: 99%
“…Paolucci et al reported an incidence of 17.1 % port site recurrence over a median period of 6 months after LC [14]. In a recent retrospective study from Memorial Sloan Kettering Cancer Centre, 69 patients after LC underwent definitive surgery with port site resection [18]. Port site recurrence was found in 13 patients (19 %) with T2 and T3 tumours.…”
Section: Laparoscopic Cholecystectomy and Port Site Recurrencementioning
confidence: 99%
“…We read with great interest the article by Dr. Maker et al, 1 in which patients undergoing definitive resection for incidental gallbladder carcinoma (GBCA) after laparoscopic cholecystectomy (LC) were divided into two groups: laparoscopic port site resected (group 1, n = 69) and laparoscopic port site not resected (group 2, n = 44). The authors reported that the incidence of port-site metastases (PSMs) was as high as 19%, and median survival of patients with T2/T3 tumors without PSMs was 42 months compared with 17 months in patients with PSMs (P = 0.005), while excision of port sites did not affect overall survival or disease recurrence, so that port-site resection should not be considered mandatory during definitive surgical treatment of incidental GBCA.…”
Section: To the Editorsmentioning
confidence: 99%
“…Port site resection does not seem to improve survival and carries a 15% risk of incisional hernia. Patients with documented port site metastasis after resection develop peritoneal disease soon after [57,65]. Therefore, routine port site resection is not recommended [41].…”
Section: Updates In Gallbladder Diseasesmentioning
confidence: 99%